PENGARUH STRATEGI METAKOGNISI TERHADAP PEMAHAMAN MEMBACA TEKS BERBENTUK DESKRIPTIF PADA MAHASISWA MANAJEMEN INFORMASI KESEHATAN INSTITUT KESEHATAN DELI HUSADA DELITUA - Herawati Br Bukit; Sulastri Br Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2020)
Doing reading comprehension needs active process in doing. The suitable teaching-learning process must achieve the objective of reading comprehension. In fact, reading skill is not easy. Lecturer should use good strategy in teaching about reading comprehension. It also happens for students that they find some hard in doing reading comprehension well. They can’t get good value for understanding the text meaning. So, the strategy is very useful to solve the difficulties in reading comprehension. This study is concerned with the reading effect about descriptive text through Metacognition strategy application. This study learns about students reading skills in descriptive text. This research is conducted based on experimental quantitative design which has two randomized subject. The population were Health Information Management students at Deli Husada Deli Tua Health Institute grade I, II and III. The random sample was taken from grade I and III as group of experimental and grade II as the control group. In every group was given pre-test and post-test in same test but the experimental group accepted the treatment of Metacognition strategy in the study. The result of this research showed that there was difference between the mean of the group of experimental and the group of control. The statistic calculation showed that t-observed (4.1) is higher than t-table (1.67) for the degree of freedom (df) 58 at the level α = 0.05 level of significance. It proves that Metacognition strategy has significantly effect on students’ reading comprehension in reading descriptive text.